1985
DOI: 10.1046/j.1537-2995.1985.25485273815.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxyethyl starch on blood coagulation, particularly factor VIII

Abstract: The effects of hydroxyethyl starch (HES) on hemostasis were investigated extensively. In order to simulate acute blood loss due to surgery or trauma, one unit (450 ml) of blood was drawn from normal healthy men. This was followed by a 1-liter infusion over 60 minutes of either 6 percent HES, 5 percent albumin, or 0.9 percent sodium chloride (NaCl) as replacement. Coagulation studies were performed before phlebotomy, before infusion and at 0, 4, 20, 27, and 92 hours following infusion. Following infusion of HES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(76 citation statements)
references
References 19 publications
2
71
0
3
Order By: Relevance
“…The progressive decrease in maximum amplitude of the starches over the dilution range (Fig. 4) can be explained by the documented dose-related inhibition of von Willebrand's factor (antigen and coagulant) by HS ⁄ sal solutions [11]. Since the maximum amplitude is largely dependent on platelet function, the different behaviour of maximum amplitude with dilution in comparison to the other thrombelastographÒ variables is entirely predictable.…”
Section: ó 2002 Blackwell Publishing Ltdmentioning
confidence: 89%
“…The progressive decrease in maximum amplitude of the starches over the dilution range (Fig. 4) can be explained by the documented dose-related inhibition of von Willebrand's factor (antigen and coagulant) by HS ⁄ sal solutions [11]. Since the maximum amplitude is largely dependent on platelet function, the different behaviour of maximum amplitude with dilution in comparison to the other thrombelastographÒ variables is entirely predictable.…”
Section: ó 2002 Blackwell Publishing Ltdmentioning
confidence: 89%
“…4,5 With large volumes of HES infused perioperatively, inhibitory effects on hemostasis, most notably on the von-Willebrand factor, have been reported. [6][7][8] Impairment of hemostasis by HES is most pronounced with large and highly substituted HES molecules, such as hetastarch, which has an average molecular weight of 450,000 dalton and a degree of substitution of 0.7 (HES 450/0.7), or after long-term use of medium molecular weight starches with a high degree of substitution (200,000 dalton; 0.62-0.66). 9,10 These HES types are characterised by delayed degradation in vivoand accumulation of HES molecules in plasma and tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology Coagulopathy with the Use of Hydroxyethyl Starch|SH Hwang, et al of this improvement was unclear, they suggested theories including hemodilution, decreased plasma viscosity, increased cardiac output, or mild elevation of clotting time 7,12,20) . The mild elevation of clotting time was ascribed to precipitation by hetastarch of factor VIII 5,7,10,15) . Studies in humans used doses lower than those necessary for the treatment of vasospasm in normal volunteers 8,15) .…”
Section: Discussionmentioning
confidence: 99%
“…The mild elevation of clotting time was ascribed to precipitation by hetastarch of factor VIII 5,7,10,15) . Studies in humans used doses lower than those necessary for the treatment of vasospasm in normal volunteers 8,15) . We thought that 500 cc/day of hetastarch was inadequate to maintain pulmonary capillary wedge pressure and hemodilution.…”
Section: Discussionmentioning
confidence: 99%